Synthesis and Characterization of Pure Infinite Layer Ni+ Nickelates: LnNiO2 (Ln = La, Nd, Pr) and La3Ni2O6. (1st April 2022) - Lokshin, Konstantin A.; Mitchell, Daniel; Lobanov, Maxim V.; Struzhkin, Viktor; Egami, Takeshi
Abstract : A synthesis method of pure low valence nickelates using a custom built H2 circulation apparatus is described. Pure infinite layer LnNiO2 (Ln = La, Nd, Pr) and La3 Ni2 O6 nickelates have been successfully prepared using this method and characterized by x-ray diffraction. Resistivity of La3 Ni2 O6 was measured as a function of temperature and pressure up to ∼2 GPa and revealed significant pressure-induced changes in both magnitude and pressure dependence of resistivity. The existence of a hidden insulator-metal transition in La3 Ni2 O6 is proposed at pressures above 100 GPa.